Feasibility of replacing the viral isolation technique in mice with RT-qPCR for the diagnosis of rabies - Marinho, Karina Miranda; Júnior, Cássio Alexandre Costa Magalhães; Júnior, Lúcio André Amorim; Vianna, Lucas Alves; Tobias, Fernando Luiz; Langoni, Hélio [UNESP]; Braga, Fabio Ribeiro; Rossi, Gabriel Augusto Marques; Vieira, Luiz Fernando Pereira (FapUNIFESP (SciELO), 2024)
Rabies is a viral encephalitis that affects mammals, including humans. Rapid and effective laboratory diagnosis of the rabies virus is critical for public health. This study evaluated the operational, technical, and financial viability of the RT-qPCR in replacement of inoculation in mice for diagnosing rabies in the laboratory routine. A total of 316 samples of mammalian brains were analyzed, 121 positives and 195 negatives, previously diagnosed by direct immunofluorescence (DIF) and mouse inoculation test (MIT). The samples were submitted to the duplex TaqMan RT-qPCR technique. The accuracy, sensitivity, and specificity of RT-qPCR were analyzed. We analyzed the costs for performing the RT-qPCR technique and compared it with the cost of MIT. The results showed 99.37% accuracy, 99.17% sensitivity, and 99.49% specificity by RT-qPCR when related to DIF and MIT results, which proved to be a robust and repeatable technique. The minimum time for a positive diagnosis was reduced in RT-qPCR (1 day) if compared to MIT (9.64 days), with a 17.7% reduction in the cost of the molecular technique. The present study demonstrated that the molecular biology technique is an efficient tool to diagnose rabies in the laboratory routine, being able to replace MIT.
Viabilidade da substituição da técnica de isolamento viral em camundongos pela RT-qPCR para o diagnóstico da raiva
Keywords: laboratory diagnosis; molecular techniques; one health; viruses; zoonosis